Valuation of ticket prices for first-division football matches in the Spanish league - Megía-Cayuela, Daniel (Wiley, 2022)
This paper measures the optimal prices of football tickets and investigates the pricing strategy of the first-division teams in the Spanish league during the 2018/2019 season. The paper develops a dual hybrid model of supply and demand based on a hedonic price approach. Fans have multiple motivations to attend the stadium, such as the quality of the opposing teams, the pre-match qualifying position, the schedule, the day of the match, the stadium facilities, and the atmosphere. Their final decision will be conditioned by the price set by the clubs. The data show a difference of almost 300% in ticket prices among clubs. The estimation results from a hedonic price equation reveal that an optimal pricing strategy is followed by only five out of 20 clubs in the league. We also quantify the percentage of overvaluation or undervaluation of ticket prices.
Keywords: Fútbol; Football tickets; Football matches; Spanish league; Prices of football tickets